2019
DOI: 10.1111/echo.14375
|View full text |Cite
|
Sign up to set email alerts
|

Elastic aortic properties in cystic fibrosis adults without cardiovascular risk factors: A case‐control study

Abstract: Introduction The presence of CFTR in smooth muscle and endothelial cells, systemic inflammation, and oxidative stress could explain vascular alterations in cystic fibrosis. Aortic elastic properties are determinants of left ventricular function by means of ventriculo‐arterial coupling and indicators of cardiovascular risk. Objectives The purpose of the present study was to compare clinically stable patients affected by cystic fibrosis without overt pulmonary hypertension with controls to evaluate aortic tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…As a small outwardly rectifying chloride channel, the effect of CFTR on vasoconstriction should get more attention. In previous studies, aortic diameter measured at valsalva sinuses was significantly higher in patients with CF mutations [37]. CFTR inhibition enhanced pressure-induced myogenic vasoconstriction [15], and aortic rings from Cftr −/− mice showed a much stronger depolarization induced vasoconstriction than those from wild-type mice [16].…”
Section: Discussionmentioning
confidence: 74%
“…As a small outwardly rectifying chloride channel, the effect of CFTR on vasoconstriction should get more attention. In previous studies, aortic diameter measured at valsalva sinuses was significantly higher in patients with CF mutations [37]. CFTR inhibition enhanced pressure-induced myogenic vasoconstriction [15], and aortic rings from Cftr −/− mice showed a much stronger depolarization induced vasoconstriction than those from wild-type mice [16].…”
Section: Discussionmentioning
confidence: 74%
“…Aortic distensibility was lower and aortic stiffness was higher in patients with cystic fibrosis compared with healthy controls, even before development of pulmonary hypertension. 14 Similar changes were observed in patients with subclinical hypothyroidism, 15 sarcoidosis, 16 a1-antitrypsin deficiency, 17 erectile dysfunction, 18 obstructive sleep apnea, 19 chronic kidney disease, 20 metabolic syndrome, 21 hypertrophic cardiomyopathy, 22 and coronary artery disease (Table 1). 23 Aortic elastance was decreased in patients with a previous history of HELLP (hemolysis, elevated liver enzymes, and low platelet count) and preeclampsia which was associated with the gestational age.…”
Section: Results Of Included Studiesmentioning
confidence: 61%
“…In a US cohort of 484 adults with CF, the prevalence of hypertension was 17% in normal weight CF adults increasing to 31% in overweight adults 84 . Studies of vascular distensibility suggest subtle changes, traditionally recognized as precursors to cardiovascular complications in non‐CF populations, may be present in CF 87,88 . Prior to the introduction of HEMT, cholesterol has been generally low in CF 89–92 .…”
Section: Survival and Prognosismentioning
confidence: 99%
“… 84 Studies of vascular distensibility suggest subtle changes, traditionally recognized as precursors to cardiovascular complications in non‐CF populations, may be present in CF. 87 , 88 Prior to the introduction of HEMT, cholesterol has been generally low in CF. 89 , 90 , 91 , 92 Although a recent study of 256 Canadian adults with CF found hyperlipidemia in a small percentage, it was not associated with CFRD or hyperglycemia.…”
Section: Survival and Prognosismentioning
confidence: 99%